PEMAHAMAN DAN FAKTOR – FAKTOR PENYEBAB KEKERASAN DALAM RUMAH TANGGA: TINJAUAN LITERATUR - Naufal Hibrizi Setiawan (Jurnal Dialektika Hukum, 2024)
Domestic violence (KDRT) is a serious problem in family law. Domestic violence can take many forms, including physical, psychological, sexual and economic. In this journal, we will discuss family law and acts of violence in the household. The author will explain the definition and forms of domestic violence, the causes of domestic violence, the impact of domestic violence on victims, and the role of family law in handling domestic violence. The research method used is literature study by collecting data from various sources, including laws, journals, articles, and books. Data analysis is carried out by identifying patterns and trends in the data, as well as presenting findings related to the topics discussed. The results of the study show that domestic violence can occur in any type of family and knows no age, gender, or educational level boundaries. Factors that cause domestic violence include individual, family, and social factors. The impact of domestic violence on victims can be in the form of physical injury, psychological damage, and social isolation. The role of family law in handling domestic violence includes prevention, treatment and recovery. The conclusion of this journal is that domestic violence is a serious problem that requires attention and action from all parties, including the government, society, and the family itself. Therefore, the government needs to increase awareness and strengthen legal protection for victims of domestic violence, as well as increase education about acts of violence in the household in the community.